Effect of Ginger and Garlic Supplement on Biochemical Profile and Sensory Meat Quality of Japanese Quail: doi: 10.5958/2581-6616.2021.00005.0 - Murthy, K. Raja Samba; Nath, D. Narendra; K, Naga Raja Kumari.; Kumar, D. Srinivas (Journal of Meat Science, 2022)
A trial was conducted to study the effect of supplementation of ginger, garlic, and their combinations in J. quail diets on biochemical profile and meat sensory quality. Day-old quail chicks (n=150) were distributed randomly into five treatments with three replicates containing ten birds each and fed with five experimental diets T1 (Basal diet/BD), T2 (BD+ 1% ginger), T3 (BD+ 2% garlic), T4 (BD+ 0.25% ginger and 0.5% garlic) and T5 (BD+ 0.5% ginger and 1% garlic) from day one to five weeks of age. Two birds per replicate were slaughtered on day 35th, and meat and blood samples were collected accordingly. The results revealed that serum total cholesterol and triglyceride values were significantly decreased in T3 and T5 groups. Serum HDL cholesterol values were significantly (p<0.05) increased in the T5 group. Serum LDL cholesterol values were significantly (p<0.05) decreased in all the treatment groups. The sensory evaluation scores were improved significantly (p<0.05) in treatment groups and the highest score for overall acceptability was observed in T5. It can be concluded that for production of meat with low lipid profile and more consumer acceptance can be possible by the incorporation of ginger and garlic combination (0.5%+ 1.0% respectively) in the diets of Japanese quail.